Stretchable optoelectronic synapses with ultraviolet to near-infrared perception for retina-inspired computing and vision-adaptive sensing - Linfeng Lan; Bo Huang; Yaping Li; Churou Wang; Jiayi Pan; Jiale Huang; Baozhong Chen; Qi zhou; Longzhen Qiu; Yafei Ding; Qing Wan; Zhong Ji; et al. (npj Flexible Electronics)
Abstract Stretchable optoelectronic synapses are attractive for intelligent perception, neuromorphic computation and visual adaptation. Here, we demonstrate a highly stretchable organic optoelectronic synaptic transistor (s-OOST) with a transconductance up to 86 mS that can simultaneously accept modulation of electrical pulses and multi-wavelength light signals (from ultraviolet to near-infrared). The s-OOST achieved highly reliable synaptic plasticity for brain-inspired computation and retina-inspired perception even under 50% tensile strain. Furthermore, the devices exibited vision-adaptive near-infrared sensing ability that was verified by single-pixel scanning imaging. Finally, the multi-wavelength (365 nm–1050 nm) optical synaptic properties were investigated under the applications of imaging memory, polychromatic optical communication and information security (coded by wavelength). This research advances the capabilities of the stretchable integrated systems with vision-adaptive sensing characteristic and computing-in-memory ability.